1992
DOI: 10.1109/55.192802
|View full text |Cite
|
Sign up to set email alerts
|

High-quality MNS capacitors prepared by jet vapor deposition at room temperature

Abstract: SAMPLE Abstruct-Thisletter reports the properties of metal-nitride-Si (MNS) capacitors in which the silicon nitride layer is produced by the jet vapor deposition (JVD) technique at room temperature. Despite the room-temperature deposition, the electrical properties of these devices are far better than any previously reported MNS capacitors. Especially remarkable is the low density of interface traps (Dit < 5 X 10"/cm2 -eV near midgap). In addition, these MNS capacitors are highly resistant to damage caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 3 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…The hydrogenated Si x N layer ͑grown with a 10-sccm H 2 flow rate͒ was found to contain about 1.5ϫ10 22 H atom/cm 3 , consistent with the higher etch rate. 26 Fowler-Nordheim tunneling in Si 3 N 4 , studied in a number of other reports [27][28][29] attests to the fact that the films prepared by ECR RPECVD are indeed of high quality. 18 Figure 7 shows the current density (J) versus electric field (E) plots of the nominally stoichiometric Si 3 N 4 , Sirich, and hydrogenated films.…”
Section: A Growth and Related Physical Propertiesmentioning
confidence: 93%
“…The hydrogenated Si x N layer ͑grown with a 10-sccm H 2 flow rate͒ was found to contain about 1.5ϫ10 22 H atom/cm 3 , consistent with the higher etch rate. 26 Fowler-Nordheim tunneling in Si 3 N 4 , studied in a number of other reports [27][28][29] attests to the fact that the films prepared by ECR RPECVD are indeed of high quality. 18 Figure 7 shows the current density (J) versus electric field (E) plots of the nominally stoichiometric Si 3 N 4 , Sirich, and hydrogenated films.…”
Section: A Growth and Related Physical Propertiesmentioning
confidence: 93%
“…[16][17][18] Extensive experimental studies have shown that the quality of GaN films is highly sensitive to the deposition method. Metalorganic chemical vapor deposition, which is based on the chemical reaction between trimethylgallium and NH 3 , can usually produce highly crystalline asgrown GaN films provided a high temperature ͑approaching 1000°C͒ is used to thermally dissociate the NH 3 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] There has been strong interest in the growth of Ba x Sr 1Ϫx TiO 3 films on silicon because of their high dielectric constant. As integrated circuit dimensions scale down, 1 the appearance of basic problems with ultrathin SiO 2 illustrates the need for new materials with higher dielectric constants.…”
Section: Introductionmentioning
confidence: 99%